Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/en14248410
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy in the Nordic Built Environment: Challenges, Opportunities and Barriers

Abstract: Within the framework Solar Heating and Cooling Programme of the International Energy Agency Task 51 “Solar Energy in Urban Planning”, case studies from Norway, Sweden, and Denmark were collected and analyzed through a comparative approach. The cases were first classified based on their urban characterization (existing and new urban areas) and then compared within the same country or in a cross-country perspective according to three areas of interest (i.e., Scale and planning process, Legislation and planning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Solar panels are installed on the green roofs, combining renewable energy generation with the benefits of temperature regulation, stormwater management, and biodiversity enhancement provided by the green roof systems. This integration demonstrates the synergies between solar energy and green infrastructure [181].…”
Section: State-of-the-art For Harnessing Solar Energy and Nature-base...mentioning
confidence: 82%
“…Solar panels are installed on the green roofs, combining renewable energy generation with the benefits of temperature regulation, stormwater management, and biodiversity enhancement provided by the green roof systems. This integration demonstrates the synergies between solar energy and green infrastructure [181].…”
Section: State-of-the-art For Harnessing Solar Energy and Nature-base...mentioning
confidence: 82%
“…A growing number of cities, mainly located in the European Union (EU) and North America, have set renewable energy targets to support the green energy transition [3]. At the municipal level, the adoption of regulations, economic incentives, and the direct financial involvement of municipalities and public authorities, combined with the storytelling of successful practices, proved to be crucial in raising public awareness and in steering private developers toward sustainable strategies [4,5]. Similarly, in the past decades, national level measures constituted a strong enabler for the exploitation of renewable energy sources (RES) [6].…”
Section: Of 31mentioning
confidence: 99%
“…Despite this growing attention to sustainable development and practices, standards or regulations that focus on solar accessibility and preservation, and the implementation of solar technology are still scarce to non-existent. Formolli et al (2021) identified weaknesses in Scandinavian solar energy legislations, challenging municipalities in promoting solar technology adoption and consequently hindering solar neighborhood development. Furthermore, the lack of such regulations can hinder the development of solar neighborhoods.…”
Section: Introductionmentioning
confidence: 99%